Urgensi Nilai dan Norma Kesadaran Berbangsa, Beragama dalam Pembelajaran Pendidikan Pancasila Kelas VI SD - Ongku Hsb, Mara (Journal of Contemporary Issue in Elementary Education, 2025)
The importance of national and religious values ​​and norms must be applied and implemented by generations so that when they grow up they have good ethics and morals and know their rights and obligations in the nation and state. This research uses qualitative research methods, namely research that emphasizes understanding a phenomenon. This research method is designed to collect, analyze and understand, the approach used is descriptive, namely explaining and aiming to describe various conditions and realities accurately and actually. Research results: The urgency of values ​​and norms of national and religious awareness in learning Pancasila education in class 6 of elementary school to form good personal character for students from class 7 to 12 of elementary school which can be manifested by in-depth religious education and following signs and norms.